Assembly of a series of zinc coordination polymers based on 5-functionalized isophthalic acids and dipyridyl. Issue 14 (16th February 2018) - Wang, Tao; Zhu, Rong-Rong; Zhang, Xiao-Feng; Yan, Tong; Wang, Quan; Feng, Jing; Zhou, Jie; Du, Lin; Zhao, Qi-Hua
Abstract : A series of zinc coordination polymers based on 5-functionalized isophthalate and flexible dipyridyl ligands have been prepared. Their thermal and luminescent properties in the solid state were also investigated. Abstract : To investigate the influence of different 5-functionalized isophthalate ligands on the self-assembly and structures of Zn(ii )-based coordination polymers (CPs), we selected four 5-functionalized isophthalate ligands coordinated with 4, 4′-bipyridyl (bpy) and Zn(ii ) salt, and four new CPs, namely, {[Zn(EtOip)(bpy)]·2H2 O} n (1 ), {[Zn(PrOip)(bpy)]·2H2 O} n (2 ), [Zn( n BuOip)(bpy)] n (3 ) and [Zn( n PeOip)(bpy)] n (4 ) (where EtOip = 5-ethoxyisophthalate, PrOip = 5- n -propoxyisophthalate, n BuOip = 5- n -butoxyisophthalate and n PeOip = 5- n -pentyloxyisophthalate), were prepared under hydrothermal conditions. Moreover, we considered changing the features of the N-ligands (length), which are expected to alter the structural diversities and properties of the resultant CPs. We used 1, 2-bis(4-pyridyl)ethene (bpe) to replace bpy; and obtained four new coordination polymers (CPs), namely, {[Zn(EtOip)(bpe)]·H2 O} n (5 ), {[Zn(PrOip)(bpe)]·H2 O} n (6 ), {[Zn( n BuOip)(bpe)]·0.5DMF} n (7 ) and [Zn( n PeOip)(bpe)] n (8 ). All of these compounds were characterized by single crystal X-ray diffraction, infrared spectroscopy, elemental analysis and powder X-ray diffraction measurements. Single-crystal X-ray analysis reveals that the structure of complexes1–4 are very similar, although different functionalized-isophthalate ligands are employed. Complexes5, 6 and7 possess a two-dimensional (2D) layered structure, and the 2D framework of complexes5 and7 can be rationalized to be a threefold interpenetrating four-connected {4 4 ·6 2 } topologicalsql network, while6 exhibits a twofold interpenetrating 4-connected 2D framework. Compound8 features a 6-connected 3D topology net based on a novel bimetallic unit [(Zn)2 (CO2 )2 ] linked by mixed n PeOip and bpe ligands. Moreover, thermal and photoluminescence properties of the synthesized complexes were also studied in detail.